Evaluasi Ruang Terbuka Hijau Privat Kawasan Perumahan Swadaya dan Perumahan Real Estat di Kelurahan Masale Kecamatan Panakkukang - Sri Wahyuningsih; Yusni Mustari; Suriana La Tanrang (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2013)
Green Open Space allocation policy (RTH) of 30% of the total land area of the city,, as required by UUPR No.26 of 2007 is not easy to be realized. The city government is unlikely to meet target of increasing green space area, if only relying on the government-owned land. Development of residential areas are increasingly widespread. A growing residential community and the active participation of the developers. Panakukkang Masale Village District is one of the city of Makassar is not spared from development. In Makassar PERDA 6 of 2006 on Spatial Makassar years 2005 to 2015 stated that this village will be developed into a region CBD (Central Bussiness District). This determination resulted in the growth of building in the Village is growing and instead of diminishing area of green space. Therefore increase the extent necessary alternative RTH RTH through Private Development. This study aims to develop the concept of the development of private green open spaces suitable to be applied in the Village Masale. The research was carried out by several studies literature as a basis for calculating the percentage of the basic building coefficient and the coefficient of private green space green base housing and residential real estate organizations, Characteristics of private green space and housing self-help residential real estate as well as the foundations for making the concept to be advised. Variables - variables used were analyzed using quantitative and qualitative approaches. The results of this research is the concept of Green Open Space development of private residential areas and residential real estate organizations in the Village Masale.